Peningkatan hasil belajar siswa dengan model Project Based Learning materi IPA benda tunggal dan campuran kelas V SDN Tangkis 1 Kecamatan Guntur Kabupaten Demak - Anita, Anita (Jurnal Kualita Pendidikan, 2024)
Thematic learning is a learning activity designed to maximize the role of students in the learning process, only in its implementation the thematic learning process tends to focus on the teacher, which results in low student learning outcomes. The thematic learning outcomes of grade 5 students in the science material of single and mixed objects are still low, due to less creative methods and learning so that students are less interested and enthusiastic in carrying out learning in class. For this problem, the author designed a Classroom Action Research (CAR) in order to improve student learning outcomes. The Classroom Action Research (CAR) implemented includes 3 stages, namely action planning, action implementation and observation, and reflection. The subjects of the study were 14 grade 5 students of SD Negeri Tangkis 1 Guntur, Demak Regency. Data collection was carried out using test and non-test techniques, which used question items and observation sheets. The results of the pre-cycle study showed that out of 14 grade 5 students who got scores above the KKM were 4 students (28% of 14 students), and those who got scores below the KKM were 10 students (71% of 14 students). The average score in the pre-cycle was 60.40. In the implementation of cycle I, it can be seen that the score above the KKM was 9 students (64% of 14 students), and those who got a score below the KKM were 5 students (36% of 14 students). The average score in cycle I was 66.29. The results of cycle II showed that there was an increase in student achievement results, 11 people or 79% completed and 3 people or 21% got a score below the KKM with an average score of 71.40. So it can be concluded that learning using the Project Based Learning method can improve the learning outcomes of 5th grade students in the science subject of Single Objects and Mixtures.